Five Priority Character Values: Content Analysis in The Independent Curriculum Mathematics Textbook in Indonesia - Ismail, Raoda; Imawan, Okky Riswandha (International Journal of Mathematics and Mathematics Education (IJMME), 2023)
Character education aims to prepare good character in welcoming better generations in the future. In Indonesia, there are five core values that form the core of the overall grades for secondary school education. This study aims to describe the five main values or characters in the teacher's manual, the five main character values in the student manual, and the suitability of the five main character values in the Independent Curriculum textbooks for teacher manuals and student manuals. This research is content analysis research with a qualitative approach through four stages, namely data acquisition, data reduction, inference, and data analysis. The source of the research data was a teacher's guide Mathematics textbook and a student guide on the Independent Curriculum in junior high schools. The unit of analysis is the five main values or characters contained in the textbook. The results of the study show that: (1) the teacher's manual develops all the character values analyzed, but has not developed religious values to the fullest; (2) the student manual develops all character values analyzed, but has not developed religious values to the fullest; and (3) the character values in the teacher's guide and student guide math textbooks are appropriate, although some characters appear in small percentage